Unpaid Plastic Bag Discount Analysis Based On Islamic Law Perspective (Case Study On Waralaba Retail X In Ponorogo) - May Shinta Retnowati; Faridl Noor Hilal; Devid Frastiawan Amir Sup (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2024)
International Seminar on Syariah and Law (INSLA 2020) E-Proceedings “Hala Tuju Syariah Dan Undang - Undang Mendepani Pandemik Covid - 19” Organized by : Faculty of Syariah and Law, Universiti Sains Islam Malaysia 27-28 October 2020